Study on Indirect Network Effects on the Construction of Electric Vehicle Charging Piles based on Game Theory Analysis. (February 2019) - Zhu, Lijing; Wang, Peize
Abstract: The development of electric vehicles (EVs) is considered as an efficient and effective way to solve China's energy shortage and air pollution problems. Due to indirect network effect, there is a mutual influence between the market scale of EVs and the market scale of EV charging piles. On one hand, the diffusion of EVs has a positive effect on the construction of charging piles. On the other hand, more charging piles will lead to further diffusion of EVs. This study focuses on the construction of EV charging piles based on indirect network effects. A three-level Stackelberg game is proposed to model the interactions between the government, the investor of charging piles, and EVs consumers. The optimal decisions of the government in terms of subsidies for EV purchasing and for charging piles construction are obtained, respectively. The charging pile construction quantity of the investors and the corresponding EV market share are also generated. Sensitivity analysis is conducted to show how the subsidy budgets impact on the subsidies allocation for purchasing EVs and charging piles construction. Finally, managerial insights are provided for the government and the EVs industry to promote the diffusion of EVs and the construction of charging piles.